2021
DOI: 10.1530/eje-20-0855
|View full text |Cite
|
Sign up to set email alerts
|

Health status is related to testosterone, estrone and body fat: moving to functional hypogonadism in adult men with HIV

Abstract: Objective. Hypogonadism is common in HIV-infected men. The relationship between health status, sex steroids and body composition is poorly known in HIV. The aim was to investigate the association between health status (comorbidities/frailty), body composition, and gonadal function in young-to-middle-aged HIV-infected men. Design. Prospective, cross-sectional, observational study. Methods. HIV-infected men aged<50 years and ongoing Highly Active Antiretroviral Therapy were enrolled. Serum total testoste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
43
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(46 citation statements)
references
References 61 publications
(125 reference statements)
3
43
0
Order By: Relevance
“…In the pre-HAART era, hypogonadism was mainly related to end-stage AIDS and poor general conditions, in conjunction with opportunistic infection [117]. In the HAART-era, hypogonadism with inappropriately low or normal LH levels (secondary hypogonadism) affects a conspicuous percentage of young to middle-aged patients and has been associated with altered body composition, virus-infection per se and HAART, and could be considered an overall expression of premature aging and patients' increased frailty [79,118].…”
Section: Pathogenesis Of Erectile Dysfunction (Ed) In Human Immunodefmentioning
confidence: 99%
“…In the pre-HAART era, hypogonadism was mainly related to end-stage AIDS and poor general conditions, in conjunction with opportunistic infection [117]. In the HAART-era, hypogonadism with inappropriately low or normal LH levels (secondary hypogonadism) affects a conspicuous percentage of young to middle-aged patients and has been associated with altered body composition, virus-infection per se and HAART, and could be considered an overall expression of premature aging and patients' increased frailty [79,118].…”
Section: Pathogenesis Of Erectile Dysfunction (Ed) In Human Immunodefmentioning
confidence: 99%
“…Indeed, an impairment of the hypothalamic-pituitary-gonadal axis is frequently reported in HIV populations, although there is a highly variable incidence, depending on both the criteria used to diagnose hypogonadism and the clinical characteristics of patients enrolled [3]. Despite this heterogeneous picture, the well-known age-related decline in testosterone (Te) serum levels seems anticipated in HIV patients [4,5]. This progressive decline could be due either to a direct viral action on glandular tissue, or to the HAART-related sequelae, although the exact pathogenic mechanism remains to be elucidated [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Despite this heterogeneous picture, the well-known age-related decline in testosterone (Te) serum levels seems anticipated in HIV patients [4,5]. This progressive decline could be due either to a direct viral action on glandular tissue, or to the HAART-related sequelae, although the exact pathogenic mechanism remains to be elucidated [4,5]. Moreover, available studies assessing the prevalence of hypogonadism in HIV-infected patients reported very variable percentages, leaving open the question of the real interconnection between hypogonadism and HIV [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, patients in this group were more frequently obese, and it is well known that obesity is among the most frequent cause of secondary/normogonadotropic hypogonadism [26]. Focusing on the known body fat redistribution due to HIV-induced lipodystrophy, the relationship between body fat (not necessarily obesity) and gonadal status was recently evaluated by De Vincentis and colleagues [27]. They found that cFT and TT were inversely related, whereas oestradiol was directly related to total body and visceral fat, and therefore hypothesized that these findings could depend on an increase of testosterone aromatization, similarly to what happens in obese hypogonadal men of general population.…”
Section: Discussionmentioning
confidence: 99%